DETERMINANTS OF POVERTY ON THE ISLAND OF SUMATRA SPATIAL DATA PANEL APPROACH - Ramadona, Midespa; hidayat, Muhammad; Hadi, M. Fikry (Universitas Muhammadiyah Bengkulu, 2025)
Th e aim of this study is to analyze the determination of poverty levels and to prove the dependence of a region. This research is a quantitative study using secondary data for the period 2017-2023, the analytical tool used is spatial data panel.this research supports the Low Level Equilibrium Trap Theory and The Vicious Cycle Of Poverty. The model used in this study is the Fixed Spatial Autoregressive (FSAR). The results show that economic growth has a significant positive effect on poverty, government expenditure has a negative and significant effect on poverty, net enrollment rate has a significant positive effect on poverty, foreign investment has a negative and significant effect on poverty, and domestic investment has a positive and significant effect on poverty. In order to overcome the problem of poverty on the Island of Sumatra, it is expected that the government needs to implement pro-poor and more inclusive policies